A elaboração de um glossário bilíngue da área de comércio tendo como subsídio a Linguística de Corpus - Rocha, Celso Fernando [UNESP] (My University, 2011)
This article aims at presenting part of the results of a terminological study concerning the sworn translation of enforceable instruments into Portuguese. Our study corpora are comprised of translated documents and texts originally written in English and in Portuguese (bill of lading, invoice and promissory note). The software WordSmith Tools generated the wordlists and we selected the term candidates from these lists. The proposed glossaries presents, apart from simple terms, fixed or semi fixed expressions, the cotext (text around the search word) extracted from the studied corpora. It was observed that most part of the fixed or semi fixed expressions are not shown by the specialty dictionaries.

O objetivo deste artigo é apresentar os resultados parciais de um levantamento terminológico referente a títulos executivos traduzidos para o português no modo juramentado. Nossos corpora são compostos por textos traduzidos, originalmente escritos em português e em inglês, referentes a conhecimento de embarque, faturas comerciais e notas promissórias. A partir das listagens geradas pelo WordSmith Tools, passamos a selecionar os candidatos a termos. Os glossários compilados trazem, além dos termos simples, expressões fixas ou semifixas, o cotexto (texto ao redor da palavra de busca) extraído dos corpora estudados. Observou-se que a maior parte das expressões fixas ou semifixas levantadas, apesar de serem recorrentes nesses tipos de documentos, não são abonadas pelos dicionários de especialidades.
The elaboration of a bilingual glossary containing commerce terms: applying the Corpus Linguistics subsidy
Keywords: Lingüística aplicada; Línguistica de corpus; Estudos da tradução baseados em corpus; Títulos executivos; applied linguistics; corpus linguistics; corpus-based translation studies; enforceable instruments